Perbedaan Konsep Tasawuf Al Ghozali Dan Ibnu Athoillah dalam Pendidikan Karakter - Arum Sekar Sari, Wuni; Nasir Riyani, Muhamad (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
The recent decline in student human resources with character and morality is one of the weaknesses in the development of student education in the field of character education. Character and morals education which is one of the reasons for producing quality generations who have character and morals as well as good social skills have recently been neglected in the world of education. This may be due to the difficulty of implementing character education for students because there is no reference to a concept that can guarantee the creation of students with good character and good morals. The progress of the world of Islamic education during the Abasiyah dynasty, to be precise in the leadership of the caliph al-Mamun, should be a role model and example for educators in this modern era so that today's education does not only prioritize cognitive and affective aspects, but also puts forward aspects of moral education that can print generation of human beings with character and virtuousness. From here we know that the deepening and study of models, as well as the concepts used by the salaf scholars in conducting character education.